Abdominal apoplexy due to rupture of inferior pancreaticoduodenal artery: A rare case of acute abdomen - Adel Zeinalpour; Amirhosein Aghili; Barmak Gholizadeh (Babol University of Medical Sciences, 2021)
Background: Abdominal apoplexy is one of the rare causes of non-traumatic intra-abdominal bleeding. This condition is usually seen in male patients in their 50s with history of hypertension. As soon as abdominal apoplexy is suspected, immediate resuscitation should be performed followed by emergent surgery. The patientchr('39')s outcome depends entirely on the clinical condition and the time interval between diagnosis and treatment. Case Presentation: Herein we present a 63-year-old man with idiopathic spontaneous intraperitoneal hemorrhage (ISIH) caused by spontaneous rupture of non-aneurysmal inferior pancreaticoduodenalartery (IPDA). Conclusion: In this report, a case of abdominal apoplexy has been presented caused by spontaneous rupture of non-aneurysmal inferior pancreaticoduodenalartery (IPDA) in a patient without any significant past medical history.